Synthesis of highly branched water-soluble polyester and its surface sizing agent strengthening mechanism - Duan Wangwang (De Gruyter, 2020)
Solvent-free and highly branched water-soluble polyester (WPET) is prepared through self-emulsification methodology, using dimethyl terephthalate (DMT), sodium dimethyl isophthalate-5-sulfonate (SIPM), trimethylolpropane (TMP), and ethylene glycol (EG) by the transesterification and polycondensation. The WPET were first utilized as surface-sizing agents for cellulose fiber paper. The structure, average molecular weights, and physical properties of the water-soluble polyester were characterized by FTIR, 1H NMR, gel permeation chromatography (GPC), dynamic light scattering (DLS), X-ray diffraction (XRD), and dynamic rheometer. The effects of polymer structure and properties, as well as the surface sizing of the paper, were investigated. WPET displayed better surface sizing properties when it was prepared under the following conditions: –COO/–OH molar ratio of 1:2, the SIPM content of 17.98%, and TMP content of 11.10%. The relationships between the WPET structure and sized paper were clearly illustrated. The mechanical properties and water resistance of sized paper did not only depend on multi-branched hydroxyl groups of the WPET chains but also relied on the interactions among polymers and fibers, as well as the high toughness of surface sizing agent. The sizing paper possesses excellent mechanical properties as well as water resistance.